PERSPEKTIF ROTASI AUDIT DAN KUALITAS AUDIT DITINJAU DARI MITRA AUDIT DAN PERUSAHAAN AUDIT (Studi Empiris pada Perusahaan Sektor Manufaktur yang Terdaftar di BEI Tahun 2018– 2022) - Khofsoh, Faza Zanuba; Syafruddin, Muchamad (Diponegoro Journal of Accounting, 2024)
This study aimed to examine the effect of the cumulative number of audit partner rotations and the cumulative number of audit firm rotations on the audit quality of company listed on the Indonesia Stock Exchange in 2018-2022. This study uses the dependent variable (absolute discretionary accruals), independent variable (cumulative number partner rotations and the cumulative number of audit firm rotations), and control variables (Tenaud, Tenfirm, CFO, ROA, ΔSale, Lev, LnTA, LOSS, LAGTA, BTM, LnAGE, and BIG 4). Research in this study was conducted using a multivariate regression analysis on the population of manufacturing companies listed in the Indonesia Stock Exchange from the year 2018 to 2022. By applying purposive sampling, 130 samples were selected. The total cumulative of audit firm rotations showed a positive coefficient, which indicated that audit firm rotations had a negative impact on increasing audit quality. The decline in quality of auditing was influenced by ineffective communication between predecessor and successor auditors which resulted in a pseudo-audit firm rotation.